2022
DOI: 10.1002/eap.2772
|View full text |Cite
|
Sign up to set email alerts
|

(Epi)genomic adaptation driven by fine geographical scale environmental heterogeneity after recent biological invasions

Abstract: Elucidating processes and mechanisms involved in rapid local adaptation to varied environments is a poorly understood but crucial component in management of invasive species. Recent studies have proposed that genetic and epigenetic variation could both contribute to ecological adaptation, yet it remains unclear on the interplay between these two components underpinning rapid adaptation in wild animal populations. To assess their respective contributions to local adaptation, we explored epigenomic and genomic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 110 publications
0
5
0
Order By: Relevance
“…temperature or salinity) have previously been reported in various invertebrates 24-28 , with significant correlation between genetic and epigenetic variation found in six of 14 studies reviewed 29 . Analyses of genetic control of epigenetic variation using methQTL have found that the fraction of epigenetic variation under direct control of DNA sequence variation 25,27 ,30 is highly variable, ranging from 2% in the threespine stickleback ( Gasterosteus aculeatus ) 30 , 3% in the Olympia oyster ( Ostrea lurida ) 27 , 19% in Ciona intestinalis 25 , 70% in human ( Homo sapiens ) 31,32 , and 88% in this study. Complementary approaches in invertebrates and vertebrates have shown that 27% of inter-individual epigenetic variation is genotype-dependent 27 and 24–35% of epigenetic variation is explained by additive genetic components 30 .…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…temperature or salinity) have previously been reported in various invertebrates 24-28 , with significant correlation between genetic and epigenetic variation found in six of 14 studies reviewed 29 . Analyses of genetic control of epigenetic variation using methQTL have found that the fraction of epigenetic variation under direct control of DNA sequence variation 25,27 ,30 is highly variable, ranging from 2% in the threespine stickleback ( Gasterosteus aculeatus ) 30 , 3% in the Olympia oyster ( Ostrea lurida ) 27 , 19% in Ciona intestinalis 25 , 70% in human ( Homo sapiens ) 31,32 , and 88% in this study. Complementary approaches in invertebrates and vertebrates have shown that 27% of inter-individual epigenetic variation is genotype-dependent 27 and 24–35% of epigenetic variation is explained by additive genetic components 30 .…”
Section: Discussionmentioning
confidence: 52%
“…Significant associations between genetic or epigenetic variation and environmental parameters (e.g. temperature or salinity) have previously been reported in various invertebrates [24][25][26][27][28] , with significant correlation between genetic and epigenetic variation found in six of 14 studies reviewed 29 . Analyses of genetic control of epigenetic variation using methQTL have found that the fraction of epigenetic variation under direct control of DNA sequence variation 25,27,30 is highly variable, ranging from 2% in the threespine stickleback (Gasterosteus aculeatus) 30 , 3% in the Olympia oyster (Ostrea lurida) 27 , 19% in Ciona intestinalis 25 , 70% in human (Homo sapiens) 31,32 , and 88% in this study.…”
Section: Discussionmentioning
confidence: 92%
“…Significant associations between genetic or epigenetic variation and environmental parameters (e.g., temperature or salinity) have previously been reported in various invertebrates (25)(26)(27)(28)(29), with a significant correlation between genetic and epigenetic variation found in 6 of 14 studies reviewed (30). MethQTL mapping revealed that the fraction of epigenetic variation associated with DNA sequence variation (26,28,31) is highly variable, ranging from 2% in the threespine stickleback (Gasterosteus aculeatus) (31), 3% in the Olympia oyster (Ostrea lurida) (28), 19% in Ciona intestinalis (26), 70% in human (Homo sapiens) (32,33), and 88% in this study. Complementary approaches in invertebrates and vertebrates have shown that 27% of interindividual epigenetic variation is genotype dependent (28) and 24-35% of the epigenetic variation is explained by additive genetic components (31).…”
Section: Discussionmentioning
confidence: 95%
“…Rapid adaptive evolution is typically associated with genetic and epigenetic changes, but the interplay between these two components underlying rapid adaptation in invasive species remains unclear. Chen et al (2023) found that the complementary interplay of genetic and epigenetic variation was involved in the local adaptation of a marine invasive model ascidian ( Ciona intestinalis ). This complementary interplay collectively promoted the rapid adaptive capacity of populations, enabling successful invasions in different environments.…”
Section: Mechanisms Of Invasion Successmentioning
confidence: 99%